2004
DOI: 10.1159/000080410
|View full text |Cite
|
Sign up to set email alerts
|

Do We Have Enough Evidence to Know when to Transfuse Erythrocytes?

Abstract: This brief article reviews the evidence regarding the oxygen delivery / oxygen carrying capacity / hemoglobin concentration at which erythrocytes should be transfused in the perioperative period. The outdated threshold of a hemoglobin concentration (Hb) of 10 g/dl or an hematocrit of 30% has been replaced by recommendations of many practice guidelines, based on clinical experience and data. Generally, in humans, these data address surrogate endpoints, rather than the primary ones of intracellular oxygenation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Many authors have reported that a human tail is an infrequent cause of a tethered cord, and in the literature, there are 18 case reports [27,28,29,30,31,32]. Certainly, it is known that a dorsal cutaneous appendage (called a human tail) is often considered to be a skin marker of underlying spinal dysraphism.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported that a human tail is an infrequent cause of a tethered cord, and in the literature, there are 18 case reports [27,28,29,30,31,32]. Certainly, it is known that a dorsal cutaneous appendage (called a human tail) is often considered to be a skin marker of underlying spinal dysraphism.…”
Section: Discussionmentioning
confidence: 99%